End of Meeting Report - ISPC 12 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2016)
The twelfth ISPC meeting was attended by 54 participants from the 15th to 16th September 2015. The report annexes contain the list of participants as well as the final agenda for the meeting.